Unfair practices in the insurance market: describing unfair clauses - Wieteska, Stanisław (Annales. Etyka w Życiu Gospodarczym, 2019)
In a market economy, the protection of consumer rights is an extremely important issue. This also applies to the insurance market where these issues are generally understood as ones related to the conclusion and execution of insurance contracts. The insured person is exposed to many dangers, being the weaker party in the insurance market, since insurance companies, as professionals, can easily impose convenient transaction terms. The article aims to identify market practices including unfair terms imposed by insurance companies. It provides examples of such unfair terms and conditions in the form of so-called abusive clauses in insurance contracts and points to the consequences of their use.